Enhancing Competitive Advantage and Service Quality Through Human Resource Performance Optimization: The Case of Dominance Coffee - Ade Trinanda; Charissa Dewi Syandra; Nathania Risma Nabilah (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2026)
This study examines how integrating human resource management and operational process control enhances service quality and competitive advantage in a Banyuwangi-based coffee shop case. The main problems identified include increased waiting time, irregular queues during peak hours, and fluctuating service consistency. The proposed solution combines attitude-based recruitment, staged training, a collaborative work culture, category-specific Service Level Agreements (SLA) for serving time, queue management based on receipt order, an expediter role, and routine briefings. The research aims to assess the impact of an integrated HR–operations approach on responsiveness, reliability, and empathy, while formulating a scalable, continuous-improvement model. Preliminary results indicate improved serving-time consistency, reduced bottlenecks during peak load, and more positive customer perceptions of service reliability. These findings highlight the importance of a feedback loop between operations and digital marketing through employees’ dual roles as content creators to accelerate service improvements.